Resin film
A resin film composition with polyimide and transparent resin, enhanced with ultraviolet absorbers and blue-shifting agents, addresses the issue of yellowing in polyimide films, ensuring high transparency and light resistance for electronic device applications.
Patent Information
- Application Number
- JP2023118825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Polyimide films used in electronic devices suffer from yellowing due to light exposure, compromising their optical characteristics, and the addition of ultraviolet absorbers to prevent this often leads to reduced transparency.
A resin film composition comprising polyimide resin, transparent resin, and additives such as ultraviolet absorbers and blue-shifting agents, formulated to maintain high light resistance while preserving transparency, with a weight ratio of 98:2 to 2:98 and specific criteria for yellow index change.
The resin film achieves excellent transparency and light resistance, minimizing yellowing and maintaining mechanical strength, suitable for applications requiring high transparency like display cover films.
Smart Images

Figure 2025015920000001 
Figure 2025015920000002 
Figure 2025015920000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin film having high light resistance. [Background technology]
[0002] There is a demand for thinner, lighter, and more flexible electronic devices, such as liquid crystal, organic electroluminescence, and electronic paper displays, as well as solar cells and touch panels. By replacing the glass materials used in these devices with film materials, they can be made more flexible, thinner, and lighter. Transparent polyimide films have been developed as glass replacement materials and are used in display substrates, cover films, and other applications.
[0003] Ordinary polyimide films are obtained by applying a polyamic acid solution, which is a polyimide precursor, to a support in the form of a film, and then subjecting the film to high-temperature treatment to remove the solvent and simultaneously perform thermal imidization. However, the heating temperature for thermal imidization is high (e.g., 300°C or higher), and coloring (increased yellowness) due to heating is likely to occur, making it difficult to apply the film to applications requiring high transparency, such as display cover films.
[0004] As a method for producing a polyimide film having high transparency, a method using polyamideimide that is soluble in an organic solvent and can be obtained by removing the organic solvent by heat treatment after casting has been proposed. For example, Patent Document 1 describes that a polyamideimide that uses fluoroalkyl-substituted benzidine as a diamine, fluoroalkyl-substituted acid dianhydride and biphenyl acid dianhydride as a tetracarboxylic acid dianhydride, and terephthalic acid chloride as a dicarboxylic acid compound has excellent transparency. When a polyimide film is used as a surface protective film for a mobile terminal device, it is assumed that the polyimide film is located at the outermost layer and is used in a state exposed to external light. However, when used for a long period of time, the polyimide resin used in the protective film tends to deteriorate in optical properties such as yellowing due to photodegradation. Addition of an ultraviolet absorbing agent is known as a method for suppressing photodegradation. The more the amount of ultraviolet absorbing agent contained in the polyimide film, the more ultraviolet light is absorbed by the ultraviolet absorbing agent, and the less ultraviolet light is absorbed by the polyimide, so that deterioration of the polyimide film due to ultraviolet light from external light is suppressed. On the other hand, it is known that if the amount of ultraviolet absorbing agent added is increased in order to increase light resistance, the film becomes colored due to light absorption by the ultraviolet absorbing agent, and transparency is reduced. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5799172 Summary of the Invention [Problem to be solved by the invention]
[0006] The polyimide film described in Patent Document 1 etc. does not become discolored during the imidization process, but there is a problem in that it may turn yellow when exposed to ultraviolet light. In view of this problem, the present invention aims to provide a resin film having high light resistance. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using the following resin composition.
[0008] 1). Resin film containing polyimide resin, transparent resin and additives.
[0009] 2) The resin film according to 1), wherein the transparent resin contains at least one selected from the group consisting of polycarbonate, acetyl cellulose, and polyester-based resins.
[0010] 3) The resin film according to 1) or 2), wherein the additive is an ultraviolet absorbing agent and a bluing agent.
[0011] 4) The resin film according to any one of 1) to 3), containing the polyimide and the transparent resin in a weight ratio in the range of 98:2 to 2:98.
[0012] 5) The resin film according to any one of 1) to 4), in which the YI before the light resistance test is -2.0 to 1.0 and the absolute value of ΔYI(B) / ΔYI(A) is 0.8 or less. (However, ΔYI(B) and ΔYI(A) are measured using a Super Xenon Weather Meter SX-75 manufactured by Suga Test Instruments at an irradiance of 180 W / m at a wavelength of 300 nm to 400 nm. 2 The surface that came into contact with the substrate when cast was designated as side B, and the surface opposite to that in contact with the substrate was designated as side A. Irradiation was performed under the above conditions from side B and side A, and YI was measured before and after irradiation. The change in YI, which indicates the degree of yellowing, is calculated according to the following formula: ΔYI(A) = (YI(side A) of film after irradiation) - (YI(side A) of film before irradiation) ΔYI(B) = (YI(side B) of film after irradiation) - (YI(side B) of film before irradiation) Effect of the Invention
[0013] According to the present invention, it is possible to provide a resin film having excellent transparency and light resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] [Resin composition] One embodiment of the present invention is a resin film containing a polyimide resin, a transparent resin, and an additive. It is particularly preferable that the additive is an ultraviolet absorbing agent and a bluing agent. <Polyimide> Polyimide is a polymer having a structural unit represented by general formula (I), and is obtained by dehydrating and cyclizing polyamic acid obtained by addition polymerization of tetracarboxylic dianhydride (hereinafter sometimes referred to as "acid dianhydride") and diamine. That is, polyimide is a polycondensation product of tetracarboxylic dianhydride and diamine, and has a structure derived from the acid dianhydride (acid dianhydride component) and a structure derived from the diamine (diamine component). Note that polyimide can also be synthesized by condensation by decarboxylation of diisocyanate and acid dianhydride.
[0015] [ka] In the general formula (I), Y is a divalent organic group, and X is a tetravalent organic group. Y is a diamine residue, which is an organic group obtained by removing two amino groups from a diamine represented by the following general formula (II). When a polyimide is synthesized using a diisocyanate, Y is a diisocyanate residue, which is an organic group obtained by removing two isocyanate groups from a diisocyanate compound. X is a tetracarboxylic dianhydride residue, which is an organic group obtained by removing two carboxy anhydride groups from a tetracarboxylic dianhydride represented by the following general formula (III).
[0016] [ka] In other words, the polyimide contains a structural unit represented by the following general formula (IIa) and a structural unit represented by the following general formula (IIIa), and has a structural unit represented by general formula (I) by forming an imide bond between the diamine-derived structure (IIa) and the tetracarboxylic dianhydride-derived structure (IIIa).
[0017] [ka] The polyimide may contain a structural unit (amide structural unit) represented by the following general formula (IV) in addition to the imide structural unit represented by general formula (I): A polyimide containing an amide structural unit in addition to the imide structural unit is also called a polyamideimide.
[0018] [ka] In the general formula (IV), Y and Z are divalent organic groups. Y is a diamine residue, as in the general formula (I). Z is a dicarboxylic acid residue, which is an organic group obtained by removing two carboxy groups from a dicarboxylic acid represented by the following general formula (V). In the synthesis of polyamideimide, a dicarboxylic acid dichloride represented by the general formula (V') is preferably used instead of a dicarboxylic acid. A dicarboxylic acid anhydride may be used instead of a dicarboxylic acid.
[0019] [ka] The diamine-derived structure represented by the above general formula (IIa) and the dicarboxylic acid-derived structure represented by the following general formula (Va) form an amide bond to form an amide structural unit represented by general formula (V). That is, polyamideimide contains the diamine-derived structure (IIa), the tetracarboxylic dianhydride-derived structure (IIIa), and the dicarboxylic acid-derived structure (Va).
[0020] [ka] The polyamideimide contains a structure of the following general formula (VI) in which a diamine-derived structure (IIa) is bonded to both ends of a dicarboxylic acid-derived structure (Va).
[0021] [ka] In general formula (VI), Y1 and Y2 are diamine residues, and Z1 is a dicarboxylic acid residue. When the portion [-Y1-NH-CO-Z1-CO-NH-Y2-] in general formula (VI) is regarded as one divalent organic group, this divalent organic group can be regarded as a diamine residue Y containing two amide bonds. That is, in general formula (I), a polyimide in which the diamine residue Y contains an amide bond is a polyamideimide, and polyamideimide can be said to be a type of polyimide. Hereinafter, unless otherwise specified, the term "polyimide" includes "polyamideimide".
[0022] As described above, the polyimide contains a diamine-derived structure (diamine component) and an acid dianhydride-derived structure (acid dianhydride component). The polyimide used in the present embodiment contains a diamine having a fluoroalkyl group in the diamine-derived structure.
[0023] (Diamine having a fluoroalkyl group) The diamine having a fluoroalkyl group includes fluoroalkyl-substituted benzidine. Specific examples of fluoroalkyl-substituted benzidine include 2-(trifluoromethyl)benzidine, 3-(trifluoromethyl)benzidine, 2,3-bis(trifluoromethyl)benzidine, 2,5-bis(trifluoromethyl)benzidine, 2,6-bis(trifluoromethyl)benzidine, 2,3,5-tris(trifluoromethyl)benzidine, 2,3,6-tris(trifluoromethyl)benzidine, 2,3,5,6-tetrakis(trifluoromethyl)benzidine, 2,2'-bis(trifluoromethyl)benzidine, 3,3'-bis(trifluoromethyl)benzidine, 2,3'-bis(trifluoromethyl)benzidine, methyl)benzidine, 2,2',3-bis(trifluoromethyl)benzidine, 2,3,3'-tris(trifluoromethyl)benzidine, 2,2',5-tris(trifluoromethyl)benzidine, 2,2',6-tris(trifluoromethyl)benzidine, 2,3',5-tris(trifluoromethyl)benzidine, 2,3',6,-tris(trifluoromethyl)benzidine, 2,2',3,3'-tetrakis(trifluoromethyl)benzidine, 2,2',5,5'-tetrakis(trifluoromethyl)benzidine, 2,2',6,6'-tetrakis(trifluoromethyl)benzidine, and the like.
[0024] Among them, fluoroalkyl-substituted benzidines having a fluoroalkyl group at the 2-position of biphenyl are preferred, and 2,2'-bis(trifluoromethyl)benzidine (hereinafter referred to as "TFMB") is particularly preferred. By having fluoroalkyl groups at the 2-position and 2'-position of biphenyl, in addition to the decrease in π electron density due to the electron-withdrawing property of the fluoroalkyl group, the bond between the two benzene rings of the biphenyl is twisted due to the steric hindrance of the fluoroalkyl group, and the planarity of the π conjugation is decreased, so that the absorption edge wavelength is shifted to a shorter wavelength, the coloration of the polyimide is reduced, and the solubility in organic solvents tends to be increased.
[0025] Examples of diamines having a fluoroalkyl group other than fluoroalkyl-substituted benzidine include diamines having an aromatic ring to which a fluoroalkyl group is bonded, such as 1,4-diamino-2-(trifluoromethyl)benzene, 1,4-diamino-2,3-bis(trifluoromethyl)benzene, 1,4-diamino-2,5-bis(trifluoromethyl)benzene, 1,4-diamino-2,6-bis(trifluoromethyl)benzene, 1,4-diamino-2,3,5-tris(trifluoromethyl)benzene, and 1,4-diamino, 2,3,5,6-tetrakis(trifluoromethyl)benzene; and diamines having a fluoroalkyl group that is not directly bonded to an aromatic ring, such as 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(3-aminophenyl)hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane.
[0026] As the diamine, a diamine containing a condensation structure of a diamine having a fluoroalkyl group and a dicarboxylic acid may be used. As described above, the amide formed by bonding a diamine to both ends of a dicarboxylic acid contains the structure of general formula (IV) and has amino groups at both ends, so it can also be considered as a diamine containing an amide structure. Therefore, the condensation product of a diamine having a fluoroalkyl group and a dicarboxylic acid can also be considered as a type of diamine having a fluoroalkyl group.
[0027] In general formula (VI), a structure in which one dicarboxylic acid and two diamines are condensed is shown, but two dicarboxylic acids and three diamines may be condensed, or three or more dicarboxylic acids and four or more diamines may be condensed.
[0028] Examples of dicarboxylic acids include aliphatic dicarboxylic acids such as adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-oxybisbenzoic acid, biphenyl-4,4'-dicarboxylic acid, and 2-fluoroterephthalic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-hexahydroterephthalic acid, hexahydroisophthalic acid, cyclohexanedicarboxylic acid, and 1,3-cyclopentanedicarboxylic acid; and heterocyclic dicarboxylic acids such as 2,5-thiophenedicarboxylic acid and 2,5-furandicarboxylic acid. In the preparation of a compound containing a condensed structure of a diamine and a dicarboxylic acid, a dicarboxylic acid dichloride or a dicarboxylic acid anhydride may be used instead of the dicarboxylic acid.
[0029] (Other diamines) The polyimide may contain, as a diamine component, a diamine that does not have a fluoroalkyl group. Examples of the diamine that does not have a fluoroalkyl group include a diamine that has an alicyclic structure, a diamine that has a fluorene structure, a diamine that has a sulfone group, and a diamine that has a fluorine-containing group other than a fluoroalkyl group.
[0030] Examples of diamines having an alicyclic structure include isophorone diamine, 1,2-cyclohexane diamine, 1,3-cyclohexane diamine, 1,4-cyclohexane diamine, 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornene, 4,4'-methylenebis(cyclohexylamine), bis(4-aminocyclohexyl)methane, 4,4'-methylenebis(2-methylcyclohexylamine), adamantane-1,3-diamine, 2,6-bis(aminomethyl)bicyclo[2.2.1]heptane, 2,5-bis(aminomethyl)bicyclo[2.2.1]heptane, 1,1-bis(4-aminophenyl)cyclohexane, etc. By using diamines having an alicyclic structure, a molded product having excellent elastic modulus, transmittance, and mechanical strength can be obtained.
[0031] An example of a diamine having a fluorene structure is 9,9-bis(4-aminophenyl)fluorene. By using a diamine having a fluorene structure, a molded product having excellent elastic modulus and mechanical strength can be obtained.
[0032] Examples of diamines having a sulfone group include 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, and 4,4'-bis[4-(4-aminophenoxy)phenoxy]diphenyl sulfone. By using a diamine having a sulfone group, the solubility and transparency of polyamideimide in a solvent may be improved, and mechanical properties such as elastic modulus and toughness may be improved. Among diaminodiphenyl sulfones, 3,3'-diaminodiphenyl sulfone (3,3'-DDS) and 4,4'-diaminodiphenyl sulfone (4,4'-DDS) are preferred. 3,3'-DDS and 4,4'-DDS may be used in combination. By using a diamine having a sulfone group, a molded article having excellent elastic modulus and mechanical strength can be obtained.
[0033] Fluorine-containing diamines include 2-fluorobenzidine, 3-fluorobenzidine, 2,3-difluorobenzidine, 2,5-difluorobenzidine, 2,6-difluorobenzidine, 2,3,5-trifluorobenzidine, 2,3,6-trifluorobenzidine, 2,3,5,6-tetrafluorobenzidine, 2,2'-difluorobenzidine, 3,3'-difluorobenzidine, 2,3'-difluorobenzidine, 2,2',3-trifluorobenzidine, 2,3,3'-trifluorobenzidine, 2,2',5-trifluorobenzidine, 2,2',6-trifluorobenzidine, 2,3',5-trifluorobenzidine, 2,3',6-trifluorobenzidine, fluorine-containing diamines, 2,2',3,3'-tetrafluorobenzidine, 2,2',5,5'-tetrafluorobenzidine, 2,2',6,6'-tetrafluorobenzidine, 2,2',3,3',6,6'-hexafluorobenzidine, 2,2',3,3',5,5',6,6'-octafluorobenzidine, 1,4-diamino-2-fluorobenzene, 1,4-diamino-2,3-difluorobenzene, 1,4-diamino-2,5-difluorobenzene, 1,4-diamino-2,6-difluorobenzene, 1,4-diamino-2,3,5-trifluorobenzene, 1,4-diamino-2,3,5,6-tetrafluorobenzene, 2,2'-dimethylbenzidine, etc. By using a fluorine-containing diamine, a molded product having excellent transmittance can be obtained.
[0034] Examples of diamines other than those mentioned above include p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, p-xylylenediamine, m-xylylenediamine, o-xylylenediamine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, and 3,3'-diaminobenzof phenone, 4,4'-diaminobenzophenone, 3,4'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2-di(3-aminophenyl)propane, 2,2-di(4-aminophenyl)propane, 2-(3-aminophenyl)-2-(4-aminophenyl)propane, 1,1-di(3-aminophenyl)-1-phenylethane, 1,1-di(4-aminophenyl)-1-phenylethane 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminobenzoyl)benzene, 1,3-bis(4-aminobenzoyl)benzene, 1,4-bis(3-aminobenzoyl)benzene, 1,4-bis(4-aminophenyl)benzene, aminobenzoyl)benzene, 1,3-bis(3-amino-α,α-dimethylbenzyl)benzene, 1,3-bis(4-amino-α,α-dimethylbenzyl)benzene, 1,4-bis(3-amino-α,α-dimethylbenzyl)benzene, 1,4-bis(4-amino-α,α-dimethylbenzyl)benzene, 2,6-bis(3-aminophenoxy)benzonitrile, 2,6-bis(3-aminophenoxy)pyridine, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-Bis(4-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, 2,2-bis[4-(3-aminophenoxy)phenyl] Propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[ 4-(4-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,4-bis[4-(3-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,4-bis[4-(4-aminophenoxy)-α,α-dimethylbenzyl]benzene, 4,4'-bis[4-(4-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 3,3'-diamino-4,4'-di Examples of aromatic diamines include phenoxybenzophenone, 3,3'-diamino-4,4'-diviphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 3,3'-diamino-4-biphenoxybenzophenone, 6,6'-bis(3-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane, and 6,6'-bis(4-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane.
[0035] Diamines include bis(aminomethyl)ether, bis(2-aminoethyl)ether, bis(3-aminopropyl)ether, bis(2-aminomethoxy)ethyl]ether, bis[2-(2-aminoethoxy)ethyl]ether, bis[2-(3-aminoprotoxy)ethyl]ether, 1,2-bis(aminomethoxy)ethane, 1,2-bis(2-aminoethoxy)ethane, 1,2-bis[2-(aminomethoxy)ethoxy]ethane, 1,2-bis[2-(2-aminoethoxy)ethoxy]ethane, ethylene glycol bis(3-aminopropyl)ether, diethylene glycol bis(3-aminopropyl)ether, triethylene glycol Chain diamines such as rubis(3-aminopropyl)ether, ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, 1,11-diaminoundecane, 1,12-diaminododecane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 1,3-bis(4-aminobutyl)tetramethyldisiloxane, α,ω-bis(3-aminopropyl)polydimethylsiloxane, and α,ω-bis(3-aminobutyl)polydimethylsiloxane can also be used.
[0036] (Bis(trimellitic anhydride) esters) The bis(trimellitic anhydride) esters are represented by the following general formula (1).
[0037] [ka] Q in the general formula (1) is any divalent organic group, and at both ends of Q, a carboxy group and a carbon atom of Q are bonded. The carbon atom bonded to the carboxy group may form a ring structure. Specific examples of the divalent organic group Q include the following (A) to (K).
[0038] [ka] R in formula (A) 1 is a fluorine atom, an alkyl group having 1 to 20 carbon atoms, or a fluoroalkyl group having 1 to 20 carbon atoms, and m is an integer of 1 to 4. The group represented by formula (A) is a group obtained by removing two hydroxyl groups from a hydroquinone derivative having a substituent on the benzene ring. Examples of hydroquinones having a substituent on the benzene ring include tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone, and 2,5-di-tert-amylhydroquinone. Note that R 1 When is a fluoroalkyl group having 1 to 20 carbon atoms, the bis(trimellitic anhydride) ester corresponds to a tetracarboxylic dianhydride having a fluoroalkyl group.
[0039] R in formula (B) 2 is a fluorine atom, an alkyl group having 1 to 20 carbon atoms, or a fluoroalkyl group having 1 to 20 carbon atoms, and n is an integer from 0 to 4. The group represented by formula (B) is a group obtained by removing two hydroxyl groups from a biphenol which may have a substituent on the benzene ring. Examples of biphenol derivatives having a substituent on the benzene ring include 2,2'-dimethylbiphenyl-4,4'-diol, 3,3'-dimethylbiphenyl-4,4'-diol, 3,3',5,5'-tetramethylbiphenyl-4,4'-diol, and 2,2',3,3',5,5'-hexamethylbiphenyl-4,4'-diol. In addition, R 2 When is a fluoroalkyl group having 1 to 20 carbon atoms, the bis(trimellitic anhydride) ester corresponds to a tetracarboxylic dianhydride having a fluoroalkyl group.
[0040] The group represented by formula (C) is a group obtained by removing two hydroxyl groups from 4,4'-isopropylidenediphenol (bisphenol A). The group represented by formula (D) is a group obtained by removing two hydroxyl groups from resorcinol.
[0041] In formula (E), p is an integer of 1 to 10. The group represented by formula (E) is a group obtained by removing two hydroxyl groups from a linear diol having 1 to 10 carbon atoms. Examples of the linear diol having 1 to 10 carbon atoms include ethylene glycol and 1,4-butanediol.
[0042] The group represented by formula (F) is a group in which two hydroxyl groups have been removed from 1,4-cyclohexanedimethanol.
[0043] R in formula (G) 3 is a hydrogen atom, a fluorine atom, an alkyl group having 1 to 20 carbon atoms, or a fluoroalkyl group having 1 to 20 carbon atoms, and q is an integer of 0 to 4. The group represented by formula (G) is a group obtained by removing two hydroxyl groups from bisphenolfluorene which may have a substituent on the benzene ring having a phenolic hydroxyl group. An example of a bisphenolfluorene derivative having a substituent on the benzene ring having a phenolic hydroxyl group is biscresolfluorene. Note that R 3 When is a fluoroalkyl group having 1 to 20 carbon atoms, the bis(trimellitic anhydride) ester corresponds to a tetracarboxylic dianhydride having a fluoroalkyl group.
[0044] The bis(trimellitic anhydride) ester is preferably an aromatic ester, and among the above (A) to (K), Q is preferably (A), (B), (C), (D), (G), (H), and (I). Among these, (A) to (D) are preferred, and (B) and (C) are particularly preferred. When Q is a group represented by general formula (B), from the viewpoint of the solubility of the polyimide, Q is preferably 2,2',3,3',5,5'-hexamethylbiphenyl-4,4'-diyl represented by the following formula (B1).
[0045] [ka] In general formula (1), the acid dianhydride in which Q is a group represented by formula (B1) is bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylic acid)-2,2',3,3',5,5'-hexamethylbiphenyl-4,4'-diyl (abbreviation: TAHMBP) represented by the following formula (2).
[0046] [ka] (Other dianhydrides) The polyimide may contain an acid dianhydride that does not have a bis(trimellitic anhydride) ester as an acid dianhydride component. Among the acid dianhydrides that do not have a bis(trimellitic anhydride) ester, examples of acid dianhydrides that have excellent compatibility with polyester resins include acid dianhydrides with fluoroalkyl groups, alicyclic tetracarboxylic dianhydrides, acid dianhydrides with ether bonds, and aromatic acid dianhydrides. The alicyclic tetracarboxylic dianhydrides may have at least one alicyclic structure, and may have both an alicyclic ring and an aromatic ring in one molecule. The alicyclic ring may be polycyclic or may have a spiro structure.
[0047] (Fluoroalkyl-containing acid dianhydrides) Examples of tetracarboxylic acid dianhydrides having a fluoroalkyl group include 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}-1,1,1,3,3,3-hexafluoropropane dianhydride, 1,4-bis(trifluoromethyl)pyromellitic dianhydride, and 4-trifluoromethylpyromellitic dianhydride. Anhydride, 3,6-di[3',5'-bis(trifluoromethyl)phenyl]pyromellitic dianhydride, 1-[3',5'-bis(trifluoromethyl)phenyl]pyromellitic dianhydride, N,N'-[[2,2,2-trifluoro-1-(trifluoromethyl)ethylidene]bis(6-hydroxy-3,1-phenylene)]bis[1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxamide], etc. Among them, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride (hereinafter referred to as "6FDA") is particularly preferred.
[0048] Examples of alicyclic tetracarboxylic dianhydrides include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,3-dimethylcyclobutane-1,2,3,4-tetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,3,4-butane tetracarboxylic dianhydride, meso-butane-1,2,3,4-tetracarboxylic dianhydride, 1,1'-bicyclohexane-3,3',4,4'tetracarboxylic acid-3,4:3',4'-dianhydride, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid dianhydride, 2,2'-binorbornane-5,5',6,6'tetracarboxylic acid dianhydride, 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic acid 1,4:2,3-dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride, 4 -(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, cyclohexane-1,4-diylbis(methylene)bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylate), 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, 5,5'-[cyclohexylidenebis(4,1-phenyleneoxy)]bis-1,3-isobenzofurandione, 5-isobe 1,3-dihydro-1,3-dioxo-,5,5'-[1,4-cyclohexanediylbis(methylene)]ester, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride, 3,5,6-tricarboxynorbornane-2-acetic acid 2,3:5,6-dianhydride, decahydro-1,4,5,8-dimethanonaphthalene-2,3,6,7-tetracarboxylic dianhydride, tricyclo[6.4.0.0(2,7)]dodecane-1,8:2,7-tetracarboxylic dianhydride, octahydro-1H,3H,8H,10H-biphenyleno[4a,4b-c:8a,8b-c']difuran-1,3,8,10-tetrone, ethylene glycol bis(hydrogenated trimellitic anhydride) ester, decahydro[2]benzopyrano[6,5,4,-def][2]benzopyran-1,3,6,8-tetrone, and the like.
[0049] Among the alicyclic tetracarboxylic dianhydrides, from the viewpoints of the transparency and mechanical strength of the polyimide, 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (H-PMDA) and 1,1'-bicyclohexane-3,3',4,4'tetracarboxylic acid-3,4:3',4'-dianhydride (H-BPDA) are preferred, and 1,2,3,4-cyclobutanetetracarboxylic dianhydride is particularly preferred.
[0050] Examples of acid dianhydrides having an ether bond that have excellent compatibility with polyester resins include 3,4'-oxydiphthalic anhydride, 4,4'-oxydiphthalic anhydride, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, etc. Among acid dianhydrides having an ether bond, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride is preferred from the viewpoint of compatibility with polyester resins.
[0051] Examples of aromatic acid anhydrides as an acid dianhydride component having excellent compatibility with polyester resins include pyromellitic dianhydride, mellophanic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 5,5'-dimethylmethylene bis(phthalic anhydride), 2,3,6,7-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 1,2,5,6-naphthalene tetracarboxylic dianhydride, terphenyl tetracarbo dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, N,N'-(9H-fluoren-9-ylidene di-4,1-phenylene)bis[1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxamide], 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 2,2-bis(4-hydroxyphenyl)propane dibenzoate-3,3',4,4'-tetracarboxylic dianhydride, 11,11-dimethyl-1H-difuro[3,4-b:3',4'-i]xanthene-1,3,7,9(11H)-tetrone, 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride, and the like.
[0052] Examples of aromatic acid dianhydrides other than those mentioned above include 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 1,3-bis[(3,4-dicarboxy)benzoyl]benzamide dianhydride, and bis(3,4-dicarboxyphenyl)methane dianhydride. benzene dianhydride, 1,4-bis[(3,4-dicarboxy)benzoyl]benzene dianhydride, 2,2-bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}propane dianhydride, 2,2-bis{4-[4-(3,4-dicarboxy)phenoxy]phenyl}propane dianhydride, 2,2-bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}propane dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl} Ketone dianhydride, 4,4'-bis[4-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, 4,4'-bis[3-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis Examples of the dianhydride include {4-[4-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 1,2,7,8-phenanthrenetetracarboxylic dianhydride, and bis(1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid)-1,4-phenylene ester.As the acid dianhydride, a chain aliphatic acid dianhydride such as ethylene tetracarboxylic dianhydride or butane tetracarboxylic dianhydride may be used.
[0053] Among the aromatic acid dianhydrides, pyromellitic dianhydride and mellophanic dianhydride are particularly preferred from the viewpoint of compatibility between polyamideimide and polyester resin.
[0054] (Dicarboxylic acid) As described above, the polyimide may be a polyamide-imide containing a structure derived from a dicarboxylic acid represented by the general formula (Va). Examples of the dicarboxylic acid include aliphatic dicarboxylic acids such as adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-oxybisbenzoic acid, biphenyl-4,4'-dicarboxylic acid, and 2-fluoroterephthalic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-hexahydroterephthalic acid, hexahydroisophthalic acid, cyclohexanedicarboxylic acid, and 1,3-cyclopentanedicarboxylic acid; and heterocyclic dicarboxylic acids such as 2,5-thiophenedicarboxylic acid and 2,5-furandicarboxylic acid. As the dicarboxylic acid, terephthalic acid and / or isophthalic acid are preferred, with terephthalic acid being particularly preferred.
[0055] In preparing polyamide-imide (polyimide containing a structure derived from dicarboxylic acid), it is preferable to use dicarboxylic acid dichloride as a monomer. As described above, polyimide may be prepared by using a compound obtained by condensing dicarboxylic acid (or a derivative such as dicarboxylic acid chloride) and diamine as a monomer.
[0056] (Polyimide composition) As described above, the polyimide used in this embodiment has a diamine containing a fluoroalkyl group and an acid dianhydride containing a bis(trimellitic anhydride) ester. In addition, both a diamine containing a fluoroalkyl group and an acid dianhydride containing a fluoroalkyl group may be used. When both the acid dianhydride and the diamine contain a fluoroalkyl group, the solubility in organic solvents and the compatibility with polyester resins tend to be improved.
[0057] In particular, since the polyimide exhibits compatibility with polyester resins in various solvents, it is preferable that the polyimide contains a diamine having a fluoroalkyl group as a diamine component, and contains a fluoroalkyl-substituted benzidine such as TFMB. The ratio of the diamine having a fluoroalkyl group to the total amount of the diamine components of the polyimide is preferably 30 mol% or more, more preferably 50 mol% or more, even more preferably 70 mol% or more, and may be 80 mol% or more, 85 mol% or more, or 90 mol% or more. It is preferable that the amount of the fluoroalkyl-substituted benzidine is within the above range, and it is particularly preferable that the amount of TFMB is within the above range.
[0058] When the polyimide contains a diamine that does not have a fluoroalkyl group as a diamine component, the diamine that does not have a fluoroalkyl group is preferably a diamine that has an alicyclic structure, a diamine that has an ether structure, a diamine that has a fluorene structure, a diamine that has a sulfone group, or a diamine that has a fluorine-containing group other than a fluoroalkyl group. The diamine that has an alicyclic structure, the diamine that has an ether structure, the diamine that has a fluorine-containing group other than a fluoroalkyl group, and the diamine that has a fluorene structure may not be included, and may be 10 mol% or more, 30 mol% or more, 50 mol% or more, 70 mol% or more, or 100 mol% based on the total amount of the diamine components of the polyimide. The diamine that has a sulfone group is preferably 80 mol% or less, preferably 60 mol% or less, and may be 40 mol% or 20 mol% or less, or may not be included, based on the total amount of the diamine components of the polyimide. If the molar ratio of the diamine that has a sulfone group is too high, the compatibility with the polyester resin may be deteriorated.
[0059] The ratio of bis(trimellitic anhydride) esters to the total amount of diamine components in the polyimide is preferably 10 mol % or more, more preferably 20 mol % or more, and may be 30 mol % or more, 50 mol % or more, 60 mol % or more, or 75 mol % or more.
[0060] When the polyimide contains an acid dianhydride other than bis(trimellitic anhydride) ester as an acid dianhydride component, the acid dianhydride is preferably an acid dianhydride having a fluoroalkyl group, an alicyclic tetracarboxylic dianhydride, an acid dianhydride having an ether structure, and an aromatic tetracarboxylic dianhydride, as an acid dianhydride component having excellent compatibility with polyester resins. The total of the acid dianhydride having a fluoroalkyl group, the bis(trimellitic anhydride) ester, the acid dianhydride having an ether structure, the alicyclic tetracarboxylic dianhydride, and the aromatic tetracarboxylic dianhydride described above is preferably 70 mol% or more, more preferably 80 mol% or more, and even more preferably 90 mol% or more, and may be 95 mol% or more or 100 mol% based on the total amount of the acid dianhydride components of the polyimide.
[0061] When the polyimide contains a dicarboxylic acid-derived structure represented by general formula (Va), i.e., when it is a polyamideimide, the amount of the dicarboxylic acid-derived structure may be 10 molar parts or more, 20 molar parts or more, 30 molar parts or more, or 40 molar parts or more relative to 100 molar parts of the tetracarboxylic dianhydride-derived structure represented by general formula (IIIa). The amount of the dicarboxylic acid-derived structure is preferably 250 molar parts or less, more preferably 200 molar parts or less, and may be 100 molar parts or less, 80 molar parts or less, 60 molar parts or less, or 50 molar parts or less relative to 100 molar parts of the tetracarboxylic dianhydride-derived structure.
[0062] When the ratio of the dicarboxylic acid-derived structure is increased, the solubility in an organic solvent tends to be improved, and the mechanical properties such as the elastic modulus and strength of the obtained molded body tend to be improved. On the other hand, when the ratio of the dicarboxylic acid-derived structure is excessively large, it may cause a decrease in compatibility with a polyester resin or a decrease in heat resistance of the resin composition.
[0063] (Preparation of Polyimide) A polyamic acid is obtained as a polyimide precursor by the reaction of an acid dianhydride with a diamine, and a polyimide is obtained by dehydration cyclization (imidization) of the polyamic acid. The method for preparing the polyamic acid is not particularly limited, and any known method can be applied. For example, a polyamic acid solution is obtained by dissolving a diamine and a tetracarboxylic dianhydride in approximately equimolar amounts (molar ratio of 90:100 to 110:100) in an organic solvent and stirring the mixture.
[0064] When preparing polyamideimide, in addition to diamine and tetracarboxylic dianhydride, dicarboxylic acid or its derivative (dicarboxylic dichloride, dicarboxylic anhydride, etc.) may be used as a monomer to prepare polyamideimide. In this case, the amount of each monomer may be adjusted so that the total amount of tetracarboxylic dianhydride and dicarboxylic acid or its derivative is approximately equimolar to the diamine.
[0065] The concentration of the polyamic acid solution is usually 5 to 35% by weight, and preferably 10 to 30% by weight. When the concentration is within this range, the polyamic acid obtained by polymerization has an appropriate molecular weight, and the polyamic acid solution has an appropriate viscosity.
[0066] In the polymerization of polyamic acid, it is preferable to add the diamine to the dianhydride in order to suppress ring-opening of the dianhydride. When adding a plurality of diamines or a plurality of dianhydrides, they may be added at once or in a plurality of portions. By adjusting the order of addition of the monomers, the physical properties of the polyimide can be controlled.
[0067] The organic solvent used for the polymerization of polyamic acid is not particularly limited as long as it does not react with diamines and acid dianhydrides and can dissolve polyamic acid. Examples of the organic solvent include urea-based solvents such as methylurea and N,N-dimethylethylurea, sulfoxide or sulfone-based solvents such as dimethylsulfoxide, diphenylsulfone, and tetramethylsulfone, amide-based solvents such as N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), N,N'-diethylacetamide, N-methyl-2-pyrrolidone (NMP), γ-butyrolactone, and hexamethylphosphoric acid triamide, halogenated alkyl solvents such as chloroform and dichloromethane, aromatic hydrocarbon solvents such as benzene and toluene, and ether-based solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, and p-cresol methyl ether. Usually, these solvents are used alone or in appropriate combination of two or more as necessary. From the viewpoint of the solubility and polymerization reactivity of the polyamic acid, DMAc, DMF, NMP, etc. are preferably used.
[0068] Polyimide is obtained by dehydration cyclization of polyamic acid. As a method for preparing polyimide from a polyamic acid solution, a method of adding a dehydrating agent, an imidization catalyst, etc. to the polyamic acid solution and proceeding with imidization in the solution can be mentioned. In order to promote the progress of imidization, the polyamic acid solution may be heated. By mixing a solution containing polyimide generated by imidization of polyamic acid with a poor solvent, polyimide precipitates as a solid. By isolating polyimide as a solid, impurities generated during the synthesis of polyamic acid, residual dehydrating agents, imidization catalysts, etc. can be washed and removed with a poor solvent, and coloring of polyimide and increase in yellowness can be prevented. In addition, by isolating polyimide as a solid, a solvent suitable for film formation, such as a low boiling point solvent, can be used when preparing a solution for producing a molded body such as a film.
[0069] The molecular weight of the polyimide (weight average molecular weight in terms of polyethylene oxide measured by gel permeation chromatography (GPC)) is preferably 10,000 to 500,000, more preferably 20,000 to 400,000, and even more preferably 40,000 to 300,000. If the molecular weight is too small, the strength of the film may be insufficient. If the molecular weight is too large, the compatibility with transparent resins or film formability may be poor.
[0070] From the viewpoint of the thermal stability and light stability of the resin composition and the film, it is preferable that the polyimide has low reactivity. The acid value of the polyimide is preferably 0.4 mmol / g or less, more preferably 0.3 mmol / g or less, and even more preferably 0.2 mmol / g or less. The acid value of the polyimide may be 0.1 mmol / g or less, 0.05 mmol / g or less, or 0.03 mmol / g or less. From the viewpoint of reducing the acid value, it is preferable that the polyimide has a high imidization rate. A small acid value tends to increase the stability of the polyimide and improve the compatibility with the transparent resin.
[0071] <Transparent resin> The type of transparent resin is not limited as long as it is compatible with polyimide and shows transparency. In addition, one or more types of transparent resin may be included. The transparent resin means a resin having a total light transmittance of 85% or more when a film having a thickness of 10 μm is produced. Examples of transparent resins include polycarbonate-based resins, polyester-based resins, acrylic-based resins, and acetyl cellulose-based resins. Among these, it is particularly preferable to include at least one selected from polycarbonate, acetyl cellulose, and polyester-based resins.
[0072] (Polyester resin) The polyester resin is composed of a diacid component and a glycol component, and the diacid component contains an aliphatic diacid component, the glycol component contains a glycol other than ethylene glycol, or both. The polymerization method is not particularly limited, and may be any known method, such as a method of obtaining an oligomer by a transesterification method or a direct esterification method, followed by melt polymerization, or further by solid-phase polymerization, but is not limited to the methods listed here.
[0073] Among the diacid components of the polyester resin, examples of aromatic diacid components include terephthalic acid, isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, and biphenyldicarboxylic acid, while examples of aliphatic diacid components include oxalic acid, succinic acid, succinic anhydride, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, fumaric acid, maleic acid, maleic anhydride, itaconic acid, citraconic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, tetrahydrophthalic acid, and anhydrides thereof.
[0074] The acid component may also include a polybasic acid having three or more functional groups, such as trimellitic acid, pyromellitic acid, benzophenone tetracarboxylic acid, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic acid anhydride, trimesic acid, ethylene glycol bis(anhydrotrimellitate), glycerol tris(anhydrotrimellitate), 1,2,3,4-butane tetracarboxylic acid, and the like.
[0075] Examples of glycol components of polyester resins include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, dipropylene glycol, neopentyl glycol, isosorbide, polycarbonate diol, 4,4'-isopropylidenebis(2-phenoxyethanol), 4,4'-isopropylidenebis(3-phenoxyethanol), 4,4'-isopropylidenebis(4-phenoxyethanol), etc. In addition to the glycol components, trifunctional or higher polyhydric alcohols such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. may also be included.
[0076] The polyester resin may be copolymerized with, as necessary, fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid, and ester-forming derivatives thereof; high-boiling monocarboxylic acids such as benzoic acid, p-tert-butylbenzoic acid, cyclohexanoic acid, and 4-hydroxyphenylstearic acid; high-boiling monoalcohols such as stearyl alcohol and 2-phenoxyethanol; and hydroxycarboxylic acids such as ε-caprolactone, lactic acid, β-hydroxybutyric acid, and p-hydroxybenzoic acid.
[0077] Examples of polyester resins include ELITEL (registered trademark) UE3200 (manufactured by Unitika Ltd., weight average molecular weight 16,000, Tg: 65°C, copolymer of terephthalic acid, isophthalic acid, neopentyl glycol, and ethylene glycol), ELITEL (registered trademark) UE3201 (manufactured by Unitika Ltd., weight average molecular weight 20,000, Tg: 65°C), ELITEL (registered trademark) UE3203 (manufactured by Unitika Ltd., weight average molecular weight 20,000, Tg: 60°C), ELITEL (registered trademark) UE3210 (manufactured by Unitika Ltd., weight average molecular weight 40,000, Tg: 45°C, copolymer of isophthalic acid, adipic acid, neopentyl glycol, and ethylene glycol), ELITEL (registered trademark) UE3215 (manufactured by Unitika Ltd., weight average molecular weight 16,000, Tg: 45°C), and ELITEL (registered trademark) UE3216 (manufactured by Unitika Ltd. , weight average molecular weight 18,000, Tg: 40°C), Elitel (registered trademark) UE3240 (manufactured by Unitika Ltd., weight average molecular weight 18,000, Tg: 40°C), Elitel (registered trademark) UE3250 (manufactured by Unitika Ltd., weight average molecular weight 18,000, Tg: 40°C), Elitel (registered trademark) UE3500 (manufactured by Unitika Ltd., weight average molecular weight 30,000, Tg: 35°C), Elitel (registered trademark) UE362 0 (manufactured by Unitika Ltd., weight average molecular weight 16,000, Tg: 42°C), Elitel (registered trademark) UE9200 (manufactured by Unitika Ltd., weight average molecular weight 15,000, Tg: 65°C), Vylon (registered trademark) UR4800 (manufactured by Toyobo Co., Ltd., weight average molecular weight 25,000, Tg: 105°C), Vylon (registered trademark) UR8300 (manufactured by Toyobo Co., Ltd., weight average molecular weight 30,000, Tg: 23°C), and the like.
[0078] From the viewpoint of the heat resistance of the resin composition and the molded body, the glass transition temperature of the polyester resin is preferably -40°C or higher, more preferably 20°C or higher, and more preferably 40°C or higher, and may be 60°C, 80°C, or 100°C or higher.
[0079] From the viewpoints of solubility in organic solvents, compatibility with the above-mentioned polyimide, and strength of molded articles, the weight average molecular weight (polystyrene equivalent) of the polyester resin is preferably 1,000 to 100,000, more preferably 2,000 to 50,000, and may be 5,000 to 40,000 or 10,000 to 30,000. If the molecular weight of the polyester resin is too small, the durability of the obtained film may decrease. If the molecular weight of the polyester resin is too high, the film formability may be poor.
[0080] The polyester resin may have solubility in commonly used organic solvents, but from the viewpoint of the solubility of polyimide and compatibility with polyimide, it is preferable that the polyester resin has solubility in highly polar solvents such as amide solvents. Since polyimide generally dissolves only in highly polar solvents such as amide solvents, dissolving the polyester resin in a highly polar solvent such as an amide solvent facilitates compatibility with polyimide.
[0081] (Acetyl cellulose resin) The acetyl cellulose resins include diacetyl cellulose and triacetyl cellulose. From the viewpoint of heat resistance, triacetyl cellulose is preferred.
[0082] From the viewpoint of heat resistance of the film, the glass transition temperature of acetyl cellulose resin is 150℃. The temperature is preferably 160° C. or higher, more preferably 160° C. or higher, and may be 170° C. or higher.
[0083] From the viewpoint of the thermal stability and light stability of the resin composition and the film, acetyl cellulose The resins have a low content of reactive functional groups such as ethylenically unsaturated groups and carboxy groups. The iodine value of the acetyl cellulose resin is 10.16 g / 100 g (0.4 m mol / g) or less, and 7.62g / 100g (0.3mmol / g) or less is more preferable. It is preferably 5.08 g / 100 g (0.2 mmol / g) or less, and more preferably 5.08 g / 100 g (0.2 mmol / g) or less. The iodine value of the cellulose-based resin is 2.54 g / 100 g (0.1 mmol / g) or less. or 1.27 g / 100 g (0.05 mmol / g) or less. The acid value of the cellulose resin is preferably 0.4 mmol / g or less, and more preferably 0.3 mmol / g or less. More preferably, the content is 0.2 mmol / g or less. The acid value is 0.1 mmol / g or less, 0.05 mmol / g or less, or 0.03 mmol / g or less. The small acid value may be less than 1 g. The stability of the acetyl cellulose resin is improved. The thermal expansion coefficient is increased and the compatibility with polyimide tends to improve.
[0084] (Acrylic resin) Examples of acrylic resins include poly(meth)acrylic acid esters such as polymethyl methacrylate. methacrylate-(meth)acrylic acid copolymer, methyl methacrylate-(meth)acrylic acid copolymer Acrylic acid ester copolymer, methyl methacrylate-acrylic acid ester-(meth)acrylic Examples of the copolymer include methyl (meth)acrylate-styrene copolymer and methyl (meth)acrylate-styrene copolymer. The resin is modified to introduce glutarimide structural units or lactone ring structural units. Good too.
[0085] From the viewpoint of transparency and compatibility with polyimide, acrylic resins are The acrylic resin preferably has acrylic as the main structural unit. The amount of methyl methacrylate relative to the total weight is preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. The acrylic resin may be methyl methacrylate or more. It may also be a homopolymer of the above.
[0086] From the viewpoint of heat resistance of the film, the glass transition temperature of the acrylic resin is preferably 110° C. or higher. The temperature may be 115° C. or higher or 120° C. or higher.
[0087] From the viewpoints of solubility in organic solvents, compatibility with the above polyimide, and film strength, The weight average molecular weight of acrylic resin (polystyrene equivalent) is 5,000 to 500,000. Preferably, 10,000 to 300,000 is more preferable, and 15,000 to 200,000 is more preferable. 0 is more preferred.
[0088] From the viewpoint of the thermal stability and light stability of the resin composition and the film, the acrylic resin is It is preferable that the content of reactive functional groups such as ethylenically unsaturated groups and carboxy groups is small. The iodine value of acrylic resin is preferably 10.16g / 100g (0.4mmol / g) or less. Preferably, 7.62 g / 100 g (0.3 mmol / g) or less, more preferably 5.08 g / 100 g (0.3 mmol / g) or less. / 100g (0.2mmol / g) or less is more preferable. The iodine value of acrylic resin is , 2.54g / 100g (0.1mmol / g) or less or 1.27g / 100g (0. The acid value of the acrylic resin may be 0.4 mmol / g or less. Preferably, the concentration is 0.3 mmol / g or less, more preferably, 0.2 mmol / g or less. The acid value of the acrylic resin is preferably 0.1 mmol / g or less, more preferably 0.05 mmol / g or less. The acid value may be 0.03 mmol / g or less. This increases the stability of the copolymer resin and tends to improve its compatibility with polyimide. .
[0089] (Polycarbonate resin) A polycarbonate resin refers to a polymer in which the bonds between monomer units are linked by carbonate bonds (-O-(C=O)-O-). From the viewpoints of compatibility with polyamideimide and solubility in methylene chloride, it is preferable for the resin to contain a structure (repeating unit) represented by general formula (3).
[0090] [ka] The weight average molecular weight of the polycarbonate resin is preferably 5,000 to 200,000, more preferably 10,000 to 100,000, and further preferably 15,000 to 50,000, from the viewpoints of compatibility with polyamideimide and strength of molded articles. Specifically, the following are TEIJIN Panlite AD-5503, K-1300Y, L-1225L, L-1225LM, L-1225Y, L-1225Z100, L-1225Z100M, L-1225ZL100, L-1250Y, L-1250Z100, LD-1000RM, LN-1010RM, LN-2250Y, LN-2250Z, LN-2520A, LN-2520HA, LN-2525ZA, LN-3000RM, LN-3050RM, LS-2250, LV-2225L, LV-2225Y, LV-2225Z, LV-225 0Y, LV-2250Z, MN-4800, MN-4800Z, MN-4805Z, Iupilon K4100, ML200, ML300, ML400 manufactured by Mitsubishi Engineering Plastics, APEC1695, APEC1697, APEC1795, APEC1797, APEC1895, APEC1897, APEC2095, APEC2097, APEC9351, APEC9371 manufactured by Covestro, and FPC-0820, FPC-0220, FPC8225, FPC2136, FPC0330 manufactured by Mitsubishi Gas Chemical.
[0091] The raw material monomers that make up polycarbonate resins include 1,2-bis(4-hydroxyphenyl)ethane, 2-(4-hydroxyphenyl)-2-(3-hydroxyphenyl)propane, 1,2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-ethyl-4-hydroxyphenyl)propane, 2,2-bis(3-n-propyl-4-hydroxyphenyl)propane, 2,2-bis(3-isopropyl-4-hydroxyphenyl)propane, 2,2-bis(3-sec-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2,2-bis(3-allyl-4-hydroxyphenyl)propane, 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl) (nyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 6,6'-dihydroxy-3,3,3',3'-tetramethylspiro(bis)indan, 2,6-dihydroxydibenzo-p-dioxin, 2,6-dihydroxyanthrene, 2,7-dihydroxyphenoxathin, 2,7-dihydroxy-9,10-dimethylphenazine, 3,6-dihydroxybenzofuran, 3,6-dihydroxya These may include toluene, tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone, 2,5-di-tert-amylhydroquinone, 2,2'-dimethylbiphenyl-4,4'-diol, 3,3'-dimethylbiphenyl-4,4'-diol, isopropylidenediphenol, 3,3',5,5'-tetramethylbiphenyl-4,4'-diol, 2,2',3,3',5,5'-hexamethylbiphenyl-4,4'-diol, resorcinol, and the like.
[0092] Furthermore, as shown in general formula (4), X can contain a cyclic structure. X can include a fluorene skeleton, a phthalimide skeleton, or an alicyclic skeleton such as cyclohexylmethylidene, 1,1-ethene, 2-[2.2.1]-bicycloheptylidene, cyclohexylidene, cyclopentylidene, cyclododecylidene, or adamantylidene. Specific examples of dihydric alcohols constituting polycarbonate resins include 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 3,3-bis(4-hydroxyphenyl)phthalimidine, 2-phenyl-3,3-bis(4-hydroxyphenyl)phthalimidine, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, and 4,4'-(3,3,5-trimethylcyclohexylidene)diphenol.
[0093] [ka] From the viewpoint of heat resistance of the film, the glass transition temperature of the polycarbonate resin is preferably 100° C. or higher, more preferably 120° C. or higher, and may be 150° C. or higher or 180° C. or higher.
[0094] <Ultraviolet absorbing agent> The transparent resin film of the present invention may contain an ultraviolet absorbing agent for the purpose of improving light resistance. The ultraviolet absorbing agent is a compound that mainly absorbs light having wavelengths in the ultraviolet region, and serves to prevent deterioration of the resin due to ultraviolet rays. Since the transparent resin film of the present invention contains a transparent polyimide resin and an acrylic resin, the ratio of the polyimide resin in the resin composition is small, so that the polyimide resin is unlikely to be decomposed by light and colored, and the film has good light resistance even without containing an ultraviolet absorber. In order to exhibit even better light resistance, such as a change in the yellowness index (YI) of the transparent resin film before and after the light resistance test of 10.0 or less, it is preferable to contain an ultraviolet absorber.
[0095] The content of the ultraviolet absorber relative to 100 parts by weight of the resin constituting the transparent resin film is preferably 0.1 parts by weight or more, more preferably 1.0 parts by weight or more, even more preferably 3.0 parts by weight or more, and particularly preferably 5.0 parts by weight or more. The content of the ultraviolet absorber is preferably 10.0 parts by weight or less, more preferably 8.0 parts by weight or less, and particularly preferably 6.0 parts by weight or less. If the content of the ultraviolet absorber is less than 0.1 parts by weight, the light resistance tends to be low, and if the content is more than 10.0 parts by weight, the yellowness index (YI) of the transparent resin film tends to be high due to the absorption of light on the short wavelength side in the visible light region shown by the ultraviolet absorber, which may be undesirable.
[0096] Examples of ultraviolet absorbents include triazine-based ultraviolet absorbents, benzotriazole-based ultraviolet absorbents, benzophenone-based ultraviolet absorbents, cyanoacrylate-based ultraviolet absorbents, and hydroxybenzoate-based ultraviolet absorbents. Among these ultraviolet absorbents, triazine-based ultraviolet absorbents or benzotriazole-based ultraviolet absorbents are preferred from the viewpoint of obtaining good light resistance, and benzotriazole-based ultraviolet absorbents are particularly preferred from the viewpoint of less coloring of transparent resin films. Only one type of ultraviolet absorbent may be used, or multiple types may be used in combination.
[0097] As the triazine-based ultraviolet absorber, commercially available triazine-based ultraviolet absorbers can be used. Examples of commercially available triazine-based ultraviolet absorbers include trade names "Tinuvin 477", "Tinuvin 460", and "Tinuvin 1600" (all manufactured by BASF), "Adeka STAB LA-46" and "Adeka STAB LA-F70" (all manufactured by ADEKA), and "Kemisorb 102" (manufactured by Chemipro Chemicals).
[0098] As the benzotriazole-based ultraviolet absorber, a commercially available benzotriazole-based ultraviolet absorber can be used. Examples of commercially available benzotriazole-based ultraviolet absorbers include trade names "Tinuvin326" and "Tinuvin360" (both manufactured by BASF), "Kemisorb279" (manufactured by Chemipro Chemicals), "Adeka STAB LA-24", "Adeka STAB LA-29", "Adeka STAB LA-31RG", "Adeka STAB LA-32", and "Adeka STAB LA-36" (all manufactured by ADEKA Corporation).
[0099] As the benzophenone-based ultraviolet absorber, a commercially available benzophenone-based ultraviolet absorber can be used. Examples of the commercially available benzophenone-based ultraviolet absorber include the product names "seesorb101" (manufactured by Shipro Chemical Co., Ltd.) and "Adekastab 1413" (manufactured by ADEKA Corporation).
[0100] When the polyimide resin has an alkyl group or a fluoroalkyl group having 1 to 20 carbon atoms on the benzene ring, particularly when the polyimide resin has a fluoroalkylalkyl group having 1 to 20 carbon atoms on the benzene ring, a combination with a triazine ultraviolet absorber or a benzotriazole ultraviolet absorber is more preferable because good light resistance can be obtained. Also, when the polyimide resin has a skeleton having distortion such as a cyclobutane structure, a combination with a triazine ultraviolet absorber or a benzotriazole ultraviolet absorber is more preferable because good light resistance can be obtained.
[0101] When the transparent resin film is a transparent resin film obtained by a solution casting method in which a solution of a resin composition containing at least a transparent resin, a polyimide resin, an ultraviolet absorber, and a solvent is applied onto a support and the solvent is removed, the ultraviolet absorber tends to be unevenly distributed on the surface in contact with the support. Therefore, in a light resistance test, the degree of yellowing when irradiated with light from the side in contact with the support tends to be smaller than the degree of yellowing when irradiated with light from the side not in contact with the support, which is preferable. The light resistance test can be performed by a known method, for example, at a black panel temperature of 83°C and an irradiance of 180 W / m at a wavelength of 300 nm to 400 nm. 2 The test can be conducted at 48 hours with xenon weathering.
[0102] <Bluing agent> The transparent resin film may contain a bluing agent. The bluing agent is an additive (dye, pigment) that absorbs light such as red, orange, and yellow, which are relatively long wavelengths in the visible light region, and adjusts the color. Examples of the bluing agent include organic pigments such as phthalocyanine blue, inorganic pigments such as ultramarine, Prussian blue, and cobalt blue, and organic dyes such as anthraquinone derivatives, indigo compounds, and methylene blue. Among these, phthalocyanine blue, ultramarine blue, anthraquinone derivatives, and indigo compounds are preferred from the viewpoint of solubility and dispersibility in resins and solvents, and phthalocyanine blue and ultramarine blue are particularly preferred from the viewpoint of heat resistance and light resistance. The bluing agent may be used alone or in combination of two or more types.
[0103] From the viewpoint of moldability of the transparent resin film, it is preferable that the bluing agent has high heat resistance. The 1% weight loss temperature is preferably 200° C. or higher, more preferably 220° C. or higher, and particularly preferably 240° C. or higher.
[0104] In order to set the transparent resin film of the present invention within a yellowness index (YI) range suitable for use as a cover film for displays, etc., the total amount of the bluing agent contained in the transparent resin film can be appropriately adjusted depending on the yellowness index (YI) required for the transparent resin film. In order to uniformly tone the transparent resin film, however, the amount is preferably 10 ppm by weight or more, and particularly preferably 20 ppm by weight or more, per 100 parts by weight of the resin constituting the transparent resin film.
[0105] The bluing agent may be any known agent. For example, anthraquinone-based bluing agents include Plast Blue 8510, Plast Blue 8514, Plast Blue 8516, Plast Blue 8520, Plast Blue 8540, Plast Blue 8580, and Plast Blue 8590 (all manufactured by Arimoto Chemical Industry Co., Ltd.), phthalocyanine blue-based bluing agents include ET 4B403 (manufactured by Dainichiseika Color & Chemicals Co., Ltd.) and BL-G207 (manufactured by Sanyo Pigment Co., Ltd.), and ultramarine blue-based bluing agents include Ultramarine Blue 51 (manufactured by Holliday Pigments).
[0106] It is desirable that the bluing agent contained in the transparent resin film does not change when exposed to light. The black panel temperature is 80°C, and the irradiance at wavelengths of 300 nm to 400 nm is 180 W / m 2 In a 48-hour xenon weather test at 500 nm to 700 nm, the change in transmittance before and after the test at the maximum wavelength (λmax) at which the transparent resin film has a maximum absorption of the bluing agent is preferably less than 0.4%, more preferably 0.3% or less, and even more preferably 0.2% or less.
[0107] <Preparation of Resin Composition> The polyimide and the transparent resin are mixed to prepare a resin composition. The ratio of the polyimide and the transparent resin in the resin composition is not particularly limited. The mixing ratio (weight ratio) of the polyimide and the transparent resin may be 98:2 to 2:98, 95:5 to 10:90, or 90:10 to 15:85. The higher the ratio of the polyimide, the higher the mechanical strength of the molded body such as a film tends to be. The higher the ratio of the transparent resin, the less coloring of the molded body such as a film tends to be, and the higher the transparency tends to be.
[0108] In order to fully utilize the effect of improving transparency by mixing polyimide and transparent resin, the ratio of the transparent resin to the total of polyimide and transparent resin is preferably 10% by weight or more, and may be 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or 50% by weight or more.
[0109] Polyimide is a polymer having a special molecular structure, and generally has low solubility in organic solvents and is not compatible with other polymers. In this embodiment, a specific polyimide is used to show high solubility in organic solvents and compatibility with transparent resins. Whether or not polyimide and transparent resin show compatibility in a solution state is confirmed by dissolving the resin composition in dimethylformamide (DMF) so that the solid content concentration is 10% by weight. If the DMF solution is not phase-separated and is transparent, it is determined that the polyimide and transparent resin show compatibility in the resin composition, and if the DMF solution is separated into two or more phases or is cloudy, it is determined that the polyimide and transparent resin do not show compatibility. The haze of a solution containing polyimide and transparent resin measured at an optical path length of 1 cm is preferably 10% or less, more preferably 5% or less, even more preferably 2% or less, and particularly preferably 1% or less.
[0110] The resin composition containing polyimide and transparent resin preferably has a single glass transition temperature in a solid state as determined by differential scanning calorimetry (DSC) and / or dynamic mechanical analysis (DMA). When the resin composition has a single glass transition temperature, the polyimide and the transparent resin can be considered to be completely compatible with each other. It is also preferable that the molded article containing polyimide and transparent resin has a single glass transition temperature.
[0111] As described above, polyimide has a fluoroalkyl group in the diamine-derived structure and a bis(trimellitic acid) ester in the acid dianhydride structure, and thus exhibits compatibility with transparent resins. Whether or not polyimide exhibits compatibility with transparent resins depends on the type and content of fluoroalkyl group-containing monomer, the type and content of bis(trimellitic acid) ester, the type and content of other monomers, and the type of transparent resin.
[0112] The resin composition may be a simple mixture of polyimide precipitated as a solid content and a transparent resin, or may be a mixture of polyimide and a transparent resin. In addition, when a polyimide solution is mixed with a poor solvent to precipitate a polyimide resin, a transparent resin may be mixed into the solution, and the resin composition obtained by mixing the polyimide and the transparent resin may be precipitated as a solid (powder).
[0113] The resin composition may be a mixed solution containing polyimide and transparent resin. The method of mixing the resins is not particularly limited, and the resins may be mixed in a solid state or in a liquid state to form a mixed solution. A polyimide solution and a transparent resin solution may be prepared separately, and the two may be mixed to prepare a mixed solution of polyimide and transparent resin.
[0114] The solvent for the solution containing the polyimide and the transparent resin may be any solvent that has the ability to dissolve both the polyimide and the transparent resin, and examples of such solvents include amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; ether-based solvents such as tetrahydrofuran and 1,4-dioxane; ketone-based solvents such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, diethyl ketone, cyclopentanone, cyclohexanone, and methylcyclohexanone; and alkyl halide solvents such as chloroform, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, chlorobenzene, dichlorobenzene, and dichloromethane. Generally, polyimides have low solubility in solvents and are often dissolved only in highly polar solvents. Therefore, amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone are more preferable as solvents. By using these solvents, the compatibility between polyimides and transparent resins may be improved. In addition, by using a solvent in which these polyimides are easily dissolved, the viscosity of the resulting solution may be reduced, resulting in improved handleability and less occurrence of appearance defects such as unevenness when producing a molded product by film formation or the like.
[0115] The resin composition may contain organic or inorganic low molecular weight compounds, polymeric compounds (e.g., epoxy resins), etc. The resin composition may contain flame retardants, ultraviolet absorbers, crosslinking agents, dyes, pigments, surfactants, leveling agents, plasticizers, fine particles, sensitizers, etc. The fine particles include organic fine particles such as polystyrene and polytetrafluoroethylene, and inorganic fine particles such as colloidal silica, carbon, and layered silicates, and may have a porous or hollow structure. The fiber reinforcing material includes carbon fiber, glass fiber, aramid fiber, etc.
[0116] <Molded articles and films> The above composition can be used to form various molded articles. Molding methods include melt methods such as injection molding, transfer molding, press molding, blow molding, inflation molding, calendar molding, and melt extrusion molding. Resin compositions containing polyimide and transparent resin tend to have a lower melt viscosity than polyimide alone, and are excellent in moldability such as injection molding, transfer molding, press molding, and melt extrusion molding.
[0117] In addition, a solution of a resin composition containing a polyimide and a transparent resin tends to have a lower solution viscosity than a solution of a polyimide alone having the same solid content concentration, which is advantageous in terms of ease of handling during transportation of the solution, high coatability, and reduction of unevenness in film thickness.
[0118] In one embodiment, the molded article is a film. The molding method of the film may be either a melting method or a solution method, but from the viewpoint of producing a film excellent in transparency and uniformity, the solution method is preferred. In the solution method, a solution containing the above-mentioned polyimide and transparent resin is applied onto a support, and the solvent is dried and removed to obtain a film.
[0119] The resin solution can be applied to the support by a known method using a bar coater or a comma coater. The support can be a glass substrate, a metal substrate such as SUS, a metal drum, a metal belt, a plastic film, or the like. From the viewpoint of improving productivity, it is preferable to use an endless support such as a metal drum or a metal belt, or a long plastic film, or the like, as the support and produce the film by roll-to-roll. When using a plastic film as the support, it is only necessary to appropriately select a material that is not dissolved in the solvent of the film-forming dope.
[0120] When a film is produced by applying a resin solution onto a support, it is preferable to filter the resin solution before application. By filtering, foreign matter in the environment and undissolved components contained in the resin solution can be removed, and defects in the appearance of the film can be eliminated.
[0121] It is preferable to perform heating when drying the solvent. The heating temperature is not particularly limited as long as the solvent can be removed and the coloring of the obtained film can be suppressed, and is appropriately set at about room temperature to 250°C, and preferably 50°C to 220°C. The heating temperature may be increased stepwise. In order to increase the efficiency of removing the solvent, the resin film may be peeled off from the support and dried after drying has progressed to a certain extent. In order to promote the removal of the solvent, heating may be performed under reduced pressure. Since the polyimide and the transparent resin are compatible with each other, the glass transition temperature is lowered compared to the polyimide alone, so that the solvent can be removed even at a lower drying temperature compared to the polyimide alone, and as a result, the coloring of the film can be reduced.
[0122] Although the toughness of a transparent resin film may be low, the strength of the film may be improved by adopting a compatible system of polyimide and transparent resin. For the purpose of improving the mechanical strength of the film, the film may be stretched in one direction or in multiple directions. When the film is stretched, the polymer chains are oriented in the stretching direction, so that the strength of the film in the in-plane direction is improved and the occurrence of breakage or cracking of the film tends to be suppressed.
[0123] In particular, in a compatible system of polyimide and transparent resin, the tensile modulus in the stretching direction tends to increase, and thus the flex resistance tends to improve.
[0124] For example, a film used as a cover film or substrate material for a foldable display device (foldable display) is repeatedly folded along the folding axis at the same location, and therefore is required to have high mechanical strength in a direction perpendicular to the folding axis. Therefore, by arranging the film so that the stretching direction is perpendicular to the folding axis, the film is unlikely to break or crack at the folding location even when folded repeatedly, and a device with high bending resistance can be provided.
[0125] The film stretching conditions are not particularly limited. For example, the stretching temperature is about ±40° C. of the glass transition temperature of the film, and may be about 120 to 300° C., 150 to 250° C., or 180 to 230° C. The stretching ratio is about 1 to 200%, and may be 5 to 150%, 10 to 120%, or 20 to 100%. The higher the stretching ratio, the higher the tensile modulus in the stretching direction tends to be. On the other hand, if the stretching ratio is excessively large, the mechanical strength in the direction perpendicular to the stretching direction tends to decrease, and the handling properties of the film may decrease.
[0126] The film may be biaxially stretched from the viewpoint of increasing the strength in any direction in the plane. The biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching. In biaxial stretching, the stretching ratio in one direction and the stretching ratio in the perpendicular direction may be the same or different. When a difference is made in the stretching ratio, the mechanical strength in the direction in which the stretching ratio is large tends to be relatively large. When a biaxially stretched film having anisotropic stretching ratio is used for a foldable device, it is preferable to arrange the direction in which the stretching ratio is large perpendicular to the folding axis.
[0127] From the viewpoint of preventing poor appearance due to adhesion of foreign matter during the film manufacturing process, it is preferable to carry out the film manufacturing process in a clean room. When manufacturing using a solution method, it is preferable to carry out the coating process, in which the solvent is not dry and environmental foreign matter is likely to adhere, in a clean room, and it is more preferable to carry out the drying process in a clean room, and it is even more preferable to carry out all processes in a clean room. The cleanliness class of the clean room specified by ISO14644-1 is preferably Class 8 or higher, and even more preferably a class higher than that.
[0128] The thickness of the film is not particularly limited and may be appropriately set depending on the application. The thickness of the film is, for example, 5 to 300 μm. From the viewpoint of obtaining a film that is both self-supporting and flexible and has high transparency, the thickness of the film is preferably 20 μm to 200 μm, and may be 30 μm to 150 μm, 40 μm to 100 μm, or 50 μm to 80 μm. The thickness of the film used as a cover film for a display is preferably 10 μm or more. When the film is stretched, the thickness after stretching is preferably within the above range.
[0129] The haze of the film is preferably 10% or less, more preferably 5% or less, even more preferably 4% or less, and may be 3.5% or less, 3% or less, 2% or less, or 1% or less. The lower the haze of the film, the more preferable. As described above, since polyimide and transparent resin are compatible with each other, a film with low haze and high transparency can be obtained. The resin composition obtained by mixing polyimide and transparent resin preferably has a haze of 10% or less when a film with a thickness of 10 μm is produced.
[0130] The total light transmittance of the film is preferably 85% or more, more preferably 90% or more. The resin composition obtained by mixing polyimide and a transparent resin preferably has a total light transmittance of 85% or more when a film having a thickness of 10 μm is produced.
[0131] The yellowness index (YI) of the film is preferably 5.0 or less, and may be 4.0 or less, 3.0 or less, 2.0 or less, 1.5 or less, or 1.0 or less. The resin composition obtained by mixing polyimide and transparent resin preferably has a yellowness index of 1.0 or less when the film is produced. As described above, by mixing polyimide and transparent resin, a film with less coloration and smaller YI can be obtained compared to the case where polyimide is used alone. In addition, when adjusting the YI with a bluing agent, it is preferably -2.0 or more, more preferably -1.0 or more, from the viewpoint of not giving an excessive blue tint.
[0132] From the viewpoint of strength, the tensile modulus of the film at room temperature is preferably 2.0 GPa or more, more preferably 3.0 GPa or more. As described above, the tensile modulus may be anisotropic, and the tensile modulus in at least one direction may be 4.0 GPa or more, 5.0 GPa or more, 5.5 GPa or more, 6.0 GPa or more, 6.5 GPa or more, or 7.0 GPa or more. The pencil hardness of the film is preferably 6B or more, preferably 4B or more, and may be 2B or more, F or more, or 2H or more. In a compatible system of polyimide and transparent resin, the pencil hardness is unlikely to decrease even if the ratio of the transparent resin is increased. Therefore, a film with little coloring and excellent transparency can be provided without significantly decreasing the excellent mechanical strength specific to polyimide.
[0133] From the viewpoint of heat resistance, the tensile modulus of the film at 150° C. is preferably 1.0 MPa or more, more preferably 10.0 MPa or more, and even more preferably 100 MPa or more. A high modulus at high temperatures is preferable because it reduces the deformation amount of the molded product in a high-temperature environment or a long-term use environment.
[0134] A film formed from a resin composition containing polyimide and a transparent resin is suitable for use as a display material because it is less colored and has high transparency. In particular, a film having high mechanical strength can be applied to a surface member such as a cover window of a display. When used in practical use, the film of the present invention may have an antistatic layer, an easy-adhesion layer, a hard coat layer, an antireflection layer, etc., on the surface. EXAMPLES
[0135] The following examples are provided to further explain the present invention, but the present invention is not limited to these examples. [Preparation of polyimide resin] (Synthesis Example 1) N,N-dimethylformamide was added as a synthesis solvent to a separable flask and stirred under a nitrogen atmosphere. TFMB (90 mol%) and TAHMBP (50 mol%) were added to the separable flask and stirred under a nitrogen atmosphere for 12 hours to synthesize an oligomer, after which 3,3'-DDS (10 mol%), ODAP (20 mol%) and CBDA (30 mol%) were added. Then, acetic acid was added and stirred under a nitrogen atmosphere for 8 hours to produce a polyamic acid solution with a solid content of 18%. Pyridine was added as an imidization catalyst to the polyamic acid solution, and after complete dispersion, acetic anhydride was added and stirred at 90°C for 3 hours. After cooling to room temperature, 2-propyl alcohol (hereinafter referred to as IPA) was added dropwise while stirring the solution to precipitate a polyimide resin. IPA was further added, and after stirring for about 30 minutes, suction filtration was performed using a Kiriyama funnel. The obtained solid was washed with IPA and then dried in a vacuum oven set at 120°C for 12 hours to obtain a polyimide resin.
[0136] (Synthesis Example 2) N,N-dimethylformamide was added as a synthesis solvent to a separable flask and stirred under a nitrogen atmosphere. TFMB (100 mol%) and 6FDA (100 mol%) were added to the separable flask. Acetic acid was then added and the mixture was stirred for 5 hours to react, resulting in a polyamic acid solution with a solid content of 18%. Pyridine was added as an imidization catalyst to the polyamic acid solution, and after complete dispersion, acetic anhydride was added and stirred at 90°C for 3 hours. After cooling to room temperature, 2-propyl alcohol (hereinafter referred to as IPA) was added dropwise while stirring the solution to precipitate a polyimide resin. IPA was further added, and after stirring for about 30 minutes, suction filtration was performed using a Kiriyama funnel. The obtained solid was washed with IPA and then dried in a vacuum oven set at 120°C for 12 hours to obtain a polyimide resin.
[0137] [Preparation of polyamide-imide resin] (Synthesis Example 3) Dimethylacetamide (hereinafter, referred to as DMAc) was added to a separable flask and stirred under a nitrogen atmosphere. TFMB (100 mol%) was added and dissolved therein, and then 6FDA (10 mol%), BPDA (30 mol%), and TPC (60 mol%) were added thereto and stirred under a nitrogen atmosphere for 18 hours to react, obtaining a polyamic acid solution with a solid content concentration of 9 wt%. Pyridine was added to the polyamic acid solution as an imidization catalyst, and after complete dispersion, acetic anhydride was added and stirred at 90°C for 3 hours. After cooling to room temperature, IPA was added dropwise while stirring the solution to precipitate a polyimide resin. Further IPA was added, and after stirring for about 30 minutes, suction filtration was performed using a Kiriyama funnel. The obtained solid was washed with IPA and then dried for 12 hours in a vacuum oven set at 120°C to obtain a polyamide-imide resin.
[0138] (Synthesis Example 4) A polyamideimide resin was obtained in the same manner as in Synthesis Example 3, except that the acid dianhydride and dicarboxylic acid to be added were changed to those shown in Table 1.
[0139] [Preparation of resin composition (solution) and production of film] Example 1 The polyimide resin obtained in Synthesis Example 1, a commercially available PET resin ("UE3200G" manufactured by Unitika, glass transition temperature: 65°C, copolymer of terephthalic acid, isophthalic acid, neopentyl glycol, and ethylene glycol, hereinafter referred to as "PET"), an ultraviolet absorber ("ADEKA STAB LA-31RG" manufactured by ADEKA Corporation, hereinafter referred to as "LA-31"), and a bluing agent ("Plast Blue 8590" manufactured by Arimoto Chemical Industry Co., Ltd., hereinafter referred to as "PB8590") were added in the weight ratios shown in Table 2 to prepare a methylene chloride solution with a solid content of 10% by weight.
[0140] The above solution was applied onto a non-alkali glass plate, and the plate was dried by heating in an air atmosphere at 60° C. for 15 minutes, at 150° C. for 30 minutes, and at 200° C. for 15 minutes to prepare a film.
[0141] (Comparative Examples 1 to 4, Reference Examples 1 to 4) A film was prepared in the same manner as in Example 1, except that the polyimide, transparent resin, and casting solvent were changed to those shown in Table 2.
[0142] [evaluation] <Haze and total light transmittance> Haze and total light transmittance (TT) were measured using a haze meter "HZ-V3" manufactured by Suga Test Instruments in accordance with JIS K7136 and JIS K7361-1. <Yellowness> The yellowness index (YI) was measured according to JIS K7373 using a Suga Test Instruments spectrophotometer "SC-P." <Light resistance test> Using a Suga Test Instruments Super Xenon Weather Meter SX-75, the irradiance was 180 W / m at wavelengths of 300 nm to 400 nm. 2 The surface that came into contact with the substrate during casting was designated side B, and the surface opposite to that in contact with the substrate was designated side A. Irradiation was performed under the above conditions from side B and side A, respectively, and the YI before and after irradiation was measured. ΔYI, which indicates the degree of yellowing, was calculated according to the following formula. YI change when irradiated from side A: ΔYI(A) = (YI(side A) of film after irradiation) - (YI(side A) of film before irradiation) YI change when irradiated from side B: ΔYI(B) = (YI(side B) of film after irradiation) - (YI(side B) of film before irradiation)
[0143] In Table 1, the compounds are described by the following abbreviations. <Diamine> TFMB: 2,2'-bis(trifluoromethyl)benzidine 3,3'-DDS: 3,3'-diaminodiphenyl sulfone <Tetracarboxylic acid dianhydride> TAHMBP: Bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylic acid)-2,2',3,3',5,5'-hexamethylbiphenyl-4,4'-diyl 6FDA: 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride CBDA: 1,2,3,4-cyclobutanetetracarboxylic dianhydride PMDA: Pyromellitic anhydride ODPA: 4,4'-oxydiphthalic dianhydride <Dicarboxylic acid chloride> TPC: Terephthalic acid chloride
[0144] [Table 1]
[0145] [Table 2] The light resistance of the film shown in Example 1 is superior to that of Reference Example 1. In addition, ΔYI(B) / ΔYI(A) is 0.8 or less, and the light resistance changes depending on the irradiated surface. In other words, it is suggested that the ultraviolet absorber is unevenly distributed on surface B. Comparative Example 1, in which the tetracarboxylic dianhydride-derived structure does not have an ester structure, has poor compatibility with PET resin, has high haze, and is insufficient in transparency. The combinations of Comparative Examples 2 to 4 also have poor compatibility with transparent resins, have high haze, and are insufficient in transparency, and do not show superiority over Reference Examples 2 to 4 that do not contain transparent resins.
Claims
1. A resin film containing polyimide resin, transparent resin, and additives.
2. The resin film according to claim 1 , wherein the transparent resin comprises at least one selected from the group consisting of polycarbonate, acetyl cellulose, and polyester-based resins.
3. 2. The resin film according to claim 1, wherein the additives are an ultraviolet absorbing agent and a bluing agent.
4. 2. The resin film according to claim 1, wherein the polyimide and the transparent resin are contained in a weight ratio ranging from 98:2 to 2:
98.
5. The resin film according to any one of claims 1 to 4, wherein the YI before the light resistance test is -2.0 to 1.0, and the absolute value of ΔYI(B) / ΔYI(A) is 0.8 or less. (ΔYI(B) and ΔYI(A) are measured using a Super Xenon Weather Meter SX-75 manufactured by Suga Test Instruments Co., Ltd., at a wavelength of 300 nm to 400 nm and an irradiance of 180 W / m 2 The surface in contact with the substrate during casting was designated as side B, and the surface opposite to the surface in contact with the substrate was designated as side A. Irradiation was performed under the above conditions from each of sides B and A, and YI was measured before and after irradiation. The change in YI, which indicates the degree of yellowing, is calculated according to the following formula: ΔYI(A)=(YI(side A) of film after irradiation)−(YI(side A) of film before irradiation) ΔYI(B)=(YI(side B) of film after irradiation)−(YI(side B) of film before irradiation)
Citation Information
Patent Citations
Concentrated egg white or salt added whole egg product and preparation thereof
JP1982099172A
Cited By
Resin composition, molded body, and film
WO2026168373A1